Co-delivery of paclitaxel and tetrandrine via iRGD peptide conjugated lipid-polymer hybrid nanoparticles overcome multidrug resistance in cancer cells - Zhang, Jinming (Sci Rep, 2017)
One of the promising strategies to overcome tumor multidrug resistance (MDR) is to deliver anticancer drug along with P-glycoprotein (P-gp) inhibitor simultaneously. To enhance the cancer cellular internalization and implement the controlled drug release, herein an iRGD peptide-modified lipid-polymer hybrid nanosystem (LPN) was fabricated to coload paclitaxel (PTX) and tetrandrine (TET) at a precise combination ratio. In this co-delivery system, PTX was covalently conjugated to poly (D,L-lactide-co-glycolide) polymeric core by redox-sensitive disulfide bond, while TET was physically capsulated spontaneously for the aim to suppress P-gp in advance by the earlier released TET in cancer cells. As a result, the PTX+TET/iRGD LPNs with a core-shell structure possessed high drug loading efficiency, stability and redox-sensitive drug release profiles. Owing to the enhanced cellular uptake and P-gp suppression mediated by TET, significantly more PTX accumulated in A2780/PTX cells treated with PTX+TET/iRGD LPNs than either free drugs or non-iRGD modified LPNs. As expected, PTX+TET/iRGD LPNs presented the highest cytotoxicity against A2780/PTX cells and effectively promoted ROS production, enhanced apoptosis and cell cycle arrests particularly. Taken together, the co-delivery system demonstrated great promise as potential treatment for MDR-related tumors based on the synergistic effects of P-gp inhibition, enhanced endocytosis and intracellular sequentially drug release.